RELATIONSHIP NUTRITIONAL STATUS AND OTHER FACTORS WITH TOODLES MOTOR DEVELOPMENT IN BEKASI - Devi Wastiti Ari; Sugiatmi (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2023)
Introduction: The Ministry of Health of the Republic of Indonesia stated that as many as 56.4% of children under the age of 5 experience growth disorders. According to the results of observations in one of the Bekasi Kindergartens, the percentage of individual completeness was 43.79%, which concluded that the child had not developed well. Aim: The purpose of this study was to determine the relationship between nutritional status, feeding practices, parenting styles and nutritional intake with the motoric development of children aged 36-59 months in PAUD Kota Bekasi.Materials and Methods: This research method uses a cross sectional design. The research was conducted at PAUD Raudhatul Jannah, KB Penguin, and BIMBA AIUEO PAUD in July-August 2022. Data was collected through interviews for the variables of feeding practices, parenting style, and nutritional care. Anthropometric measurement data collection techniques for nutritional status variables. The sample of this research was 55 toodlers aged 36-59 months by using total sampling technique. Data analysis used the chi-square test. Results: The results of the bivariate test showed that there was a relationship between nutritional status (weight/age) and motor development (p-value = 0.023), there was a relationship between nutritional status (weight/height) and motor development (p-value = 0.032), there was a relationship between feeding practices with motor development (p-value = 0.027), there is a relationship between parenting style and motor development (p-value = 0.047), and there is no relationship between nutritional intake and children's motor development (p-value = <0 .05). Conclusion: Motoric development at the age of 36-59 months is related to nutritional status, feeding practices, and parenting styles. There is no relationship between nutritional intake and motor development of children aged 36-59 months.